Omvänt eller bakvänt? Om konststycket att lägga bevisbördan i brottmål på den tilltalade, utan att det kommer bak på människorättigheterna - Träskman, Per Ole (Nordisk Tidsskrift for Kriminalvidenskab, 1998)
The International human rights demand that the prosecutor has the burden of proof. During the last years, new provisions concerning confiscation, especially in narcotic offence cases, have been introduced in some countries, e.g., England, The Netherlands and Germany. These provisions make it possible to confiscate possessions held by a suspected person, without really proving that the property originates from crime. The prosecuted person can avoid confiscation by proving that he has obtained the property in a legal way. Such a confiscation provision was introduced also in Danish law in 1997. The arguments for and against such a provision are analysed in the article, and also its compatibility with the provisions of the European Convention on Human Rights. In this respect references are made to the Salabiaku case, the Pham Hoang case and the Welch case.